EFEKTIFITAS PENYAMPAIAN INFORMASI DARI ATASAN KEPADA BAWAHAN DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI KANTOR CAMAT NAMAN TERAN - Liasta Ras Menda Sebayang; Suwardi Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
As an organization, government agencies must pay attention to human resources who are capable of being in line with technological developments and the demands of effective and efficient organizational activities. Civil servants as elements of state servants and public servants are the first and foremost elements in supporting the successful achievement of the goals of the State, for this reason the morale and work discipline of employees must receive serious attention from the leadership of the organization, which gets the attention of their subordinates. Employees are expected to carry out their duties and provide services to the community as well as not to make irregularities in their work, therefore good communication is created between superiors and subordinates. The aim of this research is to determine the effectiveness of information from superiors to subordinates in increasing work motivation of office employees Camat Naman Teran. The data used in this study are primary data collected from the field. The research method uses a qualitative approach. The informants in this study were 15 people. The theory concept used is the theory of Miles and Huberman. The conclusions in the study are based on the results of interviews with informants and key informants and are supported by observations that it is found that the effectiveness of information is not the effectiveness of information that increases work motivation; on the contrary one's motivation provides a broader view of leadership, communication and organization.